Hubungan Antara Kepercayaan Diri Dengan Kemampuan Interaksi Sosial Pada Mahasiswa Etnis Pinaesaan Salatiga - Belinda Kanine, Nindita; Aryanti Kristianingsih, Sri (Psikodinamika: Jurnal Literasi Psikologi, 2026)
Social interaction is an important skill for individuals to build relationships with others, especially in higher education environments with diverse cultural backgrounds. One internal factor that can influence social interaction skills is self-confidence. This study aims to determine the relationship between self-confidence and social interaction skills in Pinaesaan ethnic students in Salatiga. This study used a quantitative approach with a correlational design. The research sample consisted of 78 Pinaesaan ethnic students selected using an accidental sampling technique. Data collection was carried out using a self-confidence scale and a social interaction ability scale arranged on a Likert scale and distributed through Google Forms. Data analysis was performed using the Pearson Product Moment correlation test with the help of SPSS version 24. The results showed a positive and significant relationship between self-confidence and social interaction skills in Pinaesaan ethnic students in Salatiga (r = 0.328; p < 0.05). This indicates that the higher the level of self-confidence, the better the social interaction skills. Conversely, the lower the self-confidence, the lower the social interaction skills. These findings indicate that self-confidence is a psychological factor that plays an important role in improving the quality of students' social interactions in a multicultural academic environment.